Abnormal glucose homeostasis and fasting intolerance in patients with congenital porto-systemic shunts - van Albada, Mirjam E.; Shah, Pratik; Derks, Terry G. J.; Fuchs, Sabine; Jans, Judith J. M.; McLin, Valérie; van der Doef, Hubert P. J. (Frontiers in Endocrinology, 2023)
In physiological glucose homeostasis, the liver plays a crucial role in the extraction of glucose from the portal circulation and storage as glycogen to enable release through glycogenolysis upon fasting. In addition, insulin secreted by the pancreas is partly eliminated from the systemic circulation by hepatic first-pass. Therefore, patients with a congenital porto-systemic shunt present a unique combination of (a) postabsorptive hyperinsulinemic hypoglycaemia (HH) because of decreased insulin elimination and (b) fasting (ketotic) hypoglycaemia because of decreased glycogenolysis. Patients with porto-systemic shunts therefore provide important insight into the role of the portal circulation and hepatic function in different phases of glucose homeostasis.